2019
DOI: 10.1021/acs.analchem.9b01428
|View full text |Cite
|
Sign up to set email alerts
|

Machine Vision Methods, Natural Language Processing, and Machine Learning Algorithms for Automated Dispersion Plot Analysis and Chemical Identification from Complex Mixtures

Abstract: Gas-phase trace chemical detection techniques such as ion mobility spectrometry (IMS) and differential mobility spectrometry (DMS) can be used in many settings, such as evaluating the health condition of patients or detecting explosives at airports. These devices separate chemical compounds in a mixture and provide information to identify specific chemical species of interest. Further, these types of devices operate well in both controlled lab environments and in-field applications. Frequently, the commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Next, the bag-of-words (BoW) model was used. The BoW approach was adapted from NLP and information retrieval [51] as the classic and most popular form of document representation because of its simplicity and general applicability [52]. According to this technique, a collected set of keywords was explored in all the corpus documents.…”
Section: Procedure-corpus Analysismentioning
confidence: 99%
“…Next, the bag-of-words (BoW) model was used. The BoW approach was adapted from NLP and information retrieval [51] as the classic and most popular form of document representation because of its simplicity and general applicability [52]. According to this technique, a collected set of keywords was explored in all the corpus documents.…”
Section: Procedure-corpus Analysismentioning
confidence: 99%
“…5b). It should be noted that none of the previously studied algorithms 17,18 have provided this high accuracy of prediction for identifying the chemicals in a mixture. More specically, the previous machine learning studies 17,18 have reported the highest accuracy below 95%, while the CNN model, reported in this work, can reach 100% accuracy while identifying chemicals in a mixture.…”
Section: Differentiation Of Chemical Compounds With Convolutional Neu...mentioning
confidence: 98%
“…16 Signicant ongoing research focuses on formulating effective DMS data analysis strategies. 1,17,18 There are also reports showing a wide range of applications of hyphenated DMS devices, e.g., gas chromatography-DMS, 19 DMS-mass spectrometry, 5 DMS-DMS 20 for rapid separation and detection. Moreover, DMS has a simple design structure making it possible to be miniaturized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such methods have achieved good results with regard to discriminant analysis of single substances [ 11 , 12 ] but cannot be implemented well in the analysis of mixtures. The research team of Cristina E. Davis used computer vision and natural language processing to address this problem and demonstrated the ability to maintain high levels of substance-specific identification despite the presence of other substances [ 13 ]. However, their method requires manual extraction of features from the data, which introduces a subjective element and is cumbersome.…”
Section: Introductionmentioning
confidence: 99%